Corporate Involvement In People Trafficking Cases (Analysis of East Jakarta District Court Decision Number: 289/Pid.Sus/2020/PN Jkt.Tim) - Yohanes Gemilang Febrian; Tanudjaja (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The research objective in this research report is to find out the position of corporations in criminal liability for human trafficking in trafficking cases(Analysis of East Jakarta District Court Decision Number: 289/Pid.Sus/2020/PN Jkt.Tim)and to find out howLegal certainty for victims of the crime of human trafficking committed by PT. Hassindo Karya Niaga (Analysis of the East Jakarta District Court Decision Number: 289/Pid.Sus/2020/PN Jkt.Tim).The research method used is a normative juridical method where data sources come from court decisions, books and journals and the internet. The research approach used in this research is a qualitative approach. The results of this research are pActions carried out by PT. Hassindo Karya Niaga is a criminal act of human trafficking as well asthere is no legal certainty for victims of the PT Person Trafficking Crime case. Hassindo Karya Niaga due to the absence of implementation of the provision of restitution for victims contained in the decision. Actions carried out by PT. Hassindo Karya Niaga and its work constitute a criminal act of human trafficking. There is no legal certainty for victims of TIP cases committed by PT. Hassindo Karya Niaga due to the lack of implementation of the right to compensation (restitution) obtained by victims of criminal acts of human trafficking. East Jakarta District Court Decision Number: 289/Pid.Sus/2020/PN Jkt.Tim)and howLegal certainty for victims of the crime of human trafficking committed by PT. Hassindo Karya Niaga (Analysis of East Jakarta District Court Decision Number: 289/Pid.Sus/2020/PN Jkt.Tim).